Behavioral impairments and biochemical alterations in brain following exposure to WiFi radiation and aluminum in rats - Haifa Othman; Mariem Tanazefti; Mohsen Sakly; Hafedh Abdelmelek; Mohamed Ammari (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2021)
Today, WiFi radiofrequencies exposure is becoming almost unavoidable. Besides, aluminum is widely used in daily life despite its involvement in neurodegenerative diseases onset.  In this study, we investigated the effects of a 14 day exposure to WiFi radiation for 2 hours a day and aluminum chloride (AlCl3) at 200mg/Kg/day alone and associated on behavior, oxidative stress, oligoelements homeostasis and metals accumulation in the brain of rats. Results showed that WiFi radiation alone induced anxiety. Aluminum administration triggered anxiety, locomotor deficits and exploratory behavior impairments. WiFi radiation and aluminum association impaired emotional and exploratory behavior. At biochemical level, WiFi and aluminum co-exposure induced cerebral oxidative stress compared to other experimental groups. Moreover, aluminum intake increased cerebral aluminum content. WiFi radiation coupled with aluminum increased cerebral aluminum, iron and cadmium contents compared to control, WiFi and Aluminum groups, and lead content compared to WiFi and Aluminum groups. Our results reveal that WiFi radiation and aluminum, especially when associated, are harmful for the brain. Thus, it is prominent to limit the exposure to WiFi radiation and aluminum for healthy nervous system.